Competition in the Malaysian Airline Industry: An Exploratory Study using Game-Theoretical and Empirical Analysis - Ho, Kevin Swee Aun (2005)
The competitive landscape of the Malaysian airline industry is facing changes due to the presence of a low-cost carrier, AirAsia. AirAsia has gain much market share by introducing low-fares much to the expense of the national carrier, MAS. Due to the increased competition, the national carrier must react in order to stop the decline of its domestic operations. This aim of this study is to understand the strategies of the two dominant carriers in the Malaysian airline industry, MAS and AirAsia in terms of the pricing of their fares in competing routes. In order to achieve this, we examine the strategic interactions in the Malaysia airline industry by examining oligopoly conduct as well as predicting the strategic behaviour of MAS and AirAsia. A game-theoretical approached is applied to model the strategic interactions between the carriers in the domestic market taking into consideration price competition. A regression analysis is performed to test the model. Game theory predict that both firms will compete in a price war. This study found that MAS and AirAsia do react to each others’ pricing of fares in the previous period. However, we did not find any evidence of a direct price war between the carriers. The theory of oligopolistic competition seems to hold true in the local airline industry.